Passive daytime radiative cooling: Fundamentals, material designs, and applications - Chen, Meijie; Pang, Dan; Chen, Xingyu; Yan, Hongjie; Yang, Yuan (EcoMat (Beijing, China), 2022)
Passive daytime radiative cooling (PDRC) dissipates terrestrial heat to the extremely cold outer space without using any energy input or producing pollution. It has the potential to simultaneously alleviate the two major problems of energy crisis and global warming. In this review, we summarize general strategies implemented for achieving PDRC and various applications of PDRC technologies. We first introduce heat transfer processes involved in PDRC, including radiative and nonradiative heat transfer processes, to evaluate the PDRC performance. Subsequently, we summarize the general material designs used for controlling PDRC performance, such as tuning the thermal mid‐infrared emittance and solar reflectance. Finally, we discuss the diverse applications of PDRC technologies to overcome problems in space cooling, solar cell cooling, water harvesting, and electricity generation. This review discussed the fundamentals, material designs, and applications of passive daytime radiative cooling (PDRC), focusing on how to tune the thermal emittance and solar reflectance of inorganic dielectric and organic polymer materials, including selective emitters, angle‐dependent emitters, colored emitters, and switchable emitters in the PDRC. The applications of PDRC in space and solar cell cooling, water harvesting, and electricity generation are also discussed.